Honey and Mumford: Application of interactive e-LKPD to improve students' creative thinking abilities - Ferdiani, Rosita Dwi (PYTHAGORAS : Jurnal Program Studi Pendidikan Matematika, 2024)
This research aims to analyze mathematical problem-solving abilities regarding Honey and Mumford's learning style using Interactive E-LKPD on Flat-Side Space Building material. The learning style used in this research is the Honey and Mumford learning style, which consists of four types: reflector, pragmatic, theorist, and activist. This research is descriptive research using a qualitative approach with interviews and experiment-based research. To determine students' learning styles, researchers administered a learning style questionnaire classified by Honey and Mumford. The subjects of this research were 30 students in class VII A of SMPN 1 Purwosari, Pasuruan. Based on the research results, it is known that subjects with a reflector learning style need help understanding the steps for solving question number 1. Subjects with a pragmatic learning style need help understanding the steps for solving question number 1 and do not work on question number 2. Theoretical learning style subjects can understand the problem of solving questions. Number 1, but there are still errors; I still need to work on question number 2; the subject has an activist learning style and needs help understanding the steps for solving question 1. Thus, there is a need for research to determine problem-solving abilities on different topics and learning media according to students' learning styles.